Nonalcoholic steatohepatitis: risk factors and diagnosis. (October 2010) - Adams, Leon A; Feldstein, Ariel E
Nonalcoholic steatohepatitis (NASH) represents the progressive form of nonalcoholic fatty liver disease with greater potential to lead to liver-related morbidity and mortality. Diagnosing NASH mandates more intensive clinical management and consideration for clinical trials. Currently, the diagnosis of NASH requires a liver biopsy, which is invasive, with drawbacks in sampling and interpretation error. Clinical risk factors for NASH include diabetes and the metabolic syndrome; however, these are not sufficiently predictive of the condition by themselves. Routine liver aminotransaminase levels are not reliable; however, novel plasma hepatocyte apoptosis markers, either alone or in combination with clinical risk factors, are potential noninvasive diagnostic tools for the future.